PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI SHOPEE - Reza Arya Taufiqurrohman; Luluk Kholisoh; Maria Magdalena (Prosiding Seminar SeNTIK, 2023)
The existence of a marketplace is an impact of the development of the internet and information technology. Marketplace has a concept like a traditional market, except that the market is virtual. One of the marketplaces that is currently popular and developing among students is Shopee. The purpose of this study is to analyze the effect of price and promotion on purchasing decisions. The method used in this study is a quantitative approach survey method with a total of 87 respondents. Based on the results of the study, price and promotion has a partial effect on purchasing decisions, and has a simultaneously effect on purchasing decisions on significant level of 0.05. This research seems to be confirmed in many studies in the similar cases